2011
DOI: 10.1128/mcb.05310-11
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptors TR2 and TR4 Recruit Multiple Epigenetic Transcriptional Corepressors That Associate Specifically with the Embryonic β-Type Globin Promoters in Differentiated Adult Erythroid Cells

Abstract: Nuclear receptors TR2 and TR4 (TR2/TR4) were previously shown to bind in vitro to direct repeat elements in the mouse and human embryonic and fetal ␤-type globin gene promoters and to play critical roles in the silencing of these genes. By chromatin immunoprecipitation (ChIP) we show that, in adult erythroid cells, TR2/TR4 bind to the embryonic ␤-type globin promoters but not to the adult ␤-globin promoter. We purified protein complexes containing biotin-tagged TR2/TR4 from adult erythroid cells and identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
146
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(151 citation statements)
references
References 94 publications
4
146
0
1
Order By: Relevance
“…Among these, BCL11A is recognized as a master regulator of g-globin repression, 3 but other studies have also implicated SOX6, IKZF1 (Ikaros), KLF1, LSD1, RCOR-1 (CoREST), MI2B, and GATA-1 in the regulation of the fetalto-adult globin switch. [26][27][28][29][30] qRT-PCR analyses revealed that BCL11A, SOX6, GATA1, KLF1, and LSD1 were downregulated by pomalidomide, whereas levels of IKZF1, MI2B, GATA2, HDAC1, and CoREST transcripts were unaffected at day 4 of differentiation ( Figure 3A). By examining the protein levels at day 4 and day 11 of culture, we found that these proteins could be categorized into 3 different groups: those for which pomalidomide decreased their expression at first (day 4) and maintained decreased expression during differentiation (IKZF1, BCL11A, and SOX6; Figure 3B); those that were decreased at day 4 but normalized at day 11 (KLF1, GATA1, and LSD1; Figure 3C); and those that were not affected by pomalidomide (GATA2, CoREST, HDAC1; Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…Among these, BCL11A is recognized as a master regulator of g-globin repression, 3 but other studies have also implicated SOX6, IKZF1 (Ikaros), KLF1, LSD1, RCOR-1 (CoREST), MI2B, and GATA-1 in the regulation of the fetalto-adult globin switch. [26][27][28][29][30] qRT-PCR analyses revealed that BCL11A, SOX6, GATA1, KLF1, and LSD1 were downregulated by pomalidomide, whereas levels of IKZF1, MI2B, GATA2, HDAC1, and CoREST transcripts were unaffected at day 4 of differentiation ( Figure 3A). By examining the protein levels at day 4 and day 11 of culture, we found that these proteins could be categorized into 3 different groups: those for which pomalidomide decreased their expression at first (day 4) and maintained decreased expression during differentiation (IKZF1, BCL11A, and SOX6; Figure 3B); those that were decreased at day 4 but normalized at day 11 (KLF1, GATA1, and LSD1; Figure 3C); and those that were not affected by pomalidomide (GATA2, CoREST, HDAC1; Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…46 Our results show that the LSD1 inhibitor RN-1 induces high levels of HbF in baboons and are consistent with previous studies showing that LSD1 plays a critical role in γ-globin silencing as a component of the DRED complex. 25,31 However, the possibility of a role for perturbation of erythroid differentiation in the mechanism of HbF reactivation cannot be excluded, and the in vivo mechanism of action will be investigated in future studies. The level of the HbF response varies between different baboon species, 47 and, therefore, the HbF response in man and baboons may differ somewhat due to differences between species and/or physiological differences between the experimental animal model and patients with hemoglobinopathies.…”
Section: © Ferrata Storti Foundationmentioning
confidence: 99%
“…22 Recognition of the role of Direct Repeat (DR) elements in the e-and γ-globin gene promoters in repression of these respective genes led to the identification of the TR2 and TR4 non-steroidal nuclear receptor proteins that specifically bind these elements and subsequently recruit a multi-protein co-repressor complex that includes DNA methyltransferase 1 (DNMT1), lysine specific demethylase 1 (LSD1), and histone deacetylases (HDACs) to repress gene expression. [23][24][25] Both DNMT1 and LSD1 have also been identified as components of co-repressor complexes also recruited by Bcl11a. 26,27 LSD1, the first histone demethylase identified, demethylates lysine 4 (H3K4) and lysine 9 (H3K9) residues of histone H3 and represses gene expression during hematopoietic differentiation.…”
mentioning
confidence: 99%
“…By examining proteins that bind the direct repeat elements found within the promoter of the g-globin genes, the orphan nuclear hormone receptors TR2 and TR4 have been suggested to play a role as repressors of the expression of the g-globin genes (Tanabe et al 2002(Tanabe et al , 2007Cui et al 2011). Paradoxically, overexpression of TR2 and TR4 in transgenic mouse models results in elevated expression of g-globin and when overexpressed in sickle cell disease mouse models can result in partial amelioration of hematologic and pathologic symptoms of these mice (Campbell et al 2011).…”
Section: Switch From Fetal To Adult Hemoglobinmentioning
confidence: 99%